Administration of Bone Marrow-Derived Mononuclear Cells Contributed to the Reduction of Hypoxic-Ischemic Brain Injury in Neonatal Rats - Sato, Yoshiaki; Ueda, Kazuto; Kondo, Taiki; Hattori, Tetsuo; Mikrogeorgiou, Alkisti; Sugiyama, Yuichiro; Suzuki, Toshihiko; Yamamoto, Michiro; Hirata, Hitoshi; Hirakawa, Akihiro; Nakanishi, Keiko; Tsuji, Masahiro; et al. (Frontiers in Neurology, 2018)
Background/objective: Perinatal hypoxia-ischemia (HI) is an important cause of neonatal death and permanent neurological deficits. Cell therapy using various cell sources has been recently identified as a novel therapy for perinatal HI. This study aimed to investigate whether the administration of bone marrow-derived mononuclear cells (BMMNCs) ameliorated HI brain injury in a neonatal rat model. Methods: Seven-day-old rats underwent ligation of the left carotid arteries and were exposed to 8% oxygen for 60 min. BMMNCs were collected from the femurs and tibias of juvenile rats using the Ficoll–Hypaque technique and injected intravenously 24 h after the insult (1.0 × 105 cells). Activated caspase-3, as an apoptosis marker, and ED1, as an activated microglia marker, were evaluated immunohistochemically 48 h after the insult. For behavioral assessment, rotarod treadmill, gait analysis, and active avoidance tests were performed 3 weeks after the insult. After these behavioral tests (6 weeks after the insult), we evaluated the volumes of their hippocampi, cortices, thalami, striata, and globus pallidus. Results: The cell densities that were positively stained for activated caspase-3 in the hippocampi, cortices, thalami, and striata in the BMMNC-treated group decreased by 42%, 60%, 56%, and 47%, respectively, compared with those in the control group. ED1 positive cells also decreased by 35%, 39%, 47%, and 36%, respectively. In gait analysis, the BMMNC normalized the contact area of the affected hind paw widened by HI. The volumes of the affected striata and globus pallidus were significantly larger in the BMMNC group than in the control group. Conclusion: These results indicated that the injection of BMMNCs ameliorated HI brain injury in a neonatal rat model.